The Effectiveness of the Application of PhET with Inquiry Learning Model to Improve Understanding of the Concept - U. Umiliya; A. Wati; I. Mahadi (Universitas Negeri Yogyakarta, 2023)
PhET has many benefits as a means of instructional technology and media in the learning process, especially in Natural Sciences (IPA) subjects that require experimental activities. The study aimed to determine the effectiveness of using PhET simulations with inquiry learning models to increase students' conceptual understanding of static electricity. This type of research was quasi-experimental with a posttest-only control group design. The subjects were students of class IX at Public Junior High School (SMPN) 1 Tebing Tinggi for the 2022/2023 academic year. Data collection used concept comprehension question sheets that had been prepared by indicators of conceptual understanding and indicators of competency in static electricity material. The study showed the average value of the indicator in the experimental group was higher than the control group. This study concludes that learning using the inquiry learning model assisted by PhET simulation can facilitate students to learn independently, and students can conduct virtual experiments as an alternative solution to the limited facilities of the schools.